2009
DOI: 10.1111/j.1464-410x.2009.08368.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perspective of botulinum toxin‐A as a long‐term treatment option for neurogenic detrusor overactivity secondary to spinal cord injury

Abstract: OBJECTIVE To evaluate patients’ perspective on whether they would consider botulinum toxin‐A (BTX‐A) injections as a long‐term treatment option for managing their neurogenic detrusor overactivity (NDO) secondary to spinal cord injury (SCI). PATIENTS AND METHODS In all, 72 patients with SCI and urodynamically confirmed NDO refractory to anticholinergics, who have had at least one or more injections with BTX‐A were invited to participate in a 5‐min telephone questionnaire covering various aspects of their treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…Nevertheless, when the dryness rate is compared between the two groups of patients (IDO and NDO) (Figure 1), it would need one extra patient to become dry to induce a p value of less than 0.05 and make the result statistically significant. The incidence of UTIs in IDO patients is comparable to the published literature, 19 but the NDO group showed less UTIs than the IDO group. 4.7% in NDO group compared to 6.06% in IDO group.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, when the dryness rate is compared between the two groups of patients (IDO and NDO) (Figure 1), it would need one extra patient to become dry to induce a p value of less than 0.05 and make the result statistically significant. The incidence of UTIs in IDO patients is comparable to the published literature, 19 but the NDO group showed less UTIs than the IDO group. 4.7% in NDO group compared to 6.06% in IDO group.…”
Section: Discussionsupporting
confidence: 84%
“…However, statistically it is still significant and comparable as the previous studies were based on less number of patients. 16,19 In addition, to keep consistency with our procedure and avoid mistakes we only included patients from the same centre and who had their treatments given by the same two surgeons. This has resulted in an unequal number, but, we have fewer variables for the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to significant clinical and urodynamic improvements, this study showed that a sustained QoL could be achieved by repeated detrusor BoNT/A injections over a 6-year period. 44 Hori et al 62 evaluated patients' perspective of BoNT/A (Dysport ® (abobotulinumtoxinA) 750 U and 1000 U) in 72 individuals with SCI who had urodynamically confirmed NDO and poor results with anticholinergic medications. Patients who had had one or more injections with BoNT/A were invited to participate in a 5-minute telephone questionnaire and rated their satisfaction on a scale of 1-10, with 10 being "very satisfied".…”
Section: Qol and Patient Perspectivementioning
confidence: 99%
“…This occurred in patients receiving intradetrusor injections of Dysport ® (abotulinumtoxinA) 1000 U doses, but none when the dose was reduced to 750 U. 62 Grosse et al reported that four patients had transient weakness in the trunk and/or lower extremities, all after Dysport ® injections. 39 In one of them the weakness lasted for 2 months after 1000 U/10 ml, for two the weakness lasted for 4 weeks after 750 U/10 ml -one of those had two previous Botox ® injections 300 U/ 15 ml without problems.…”
mentioning
confidence: 99%